Similar Pain Intensity Reductions and Trunk Strength Improvements Following Whole-Body Electromyostimulation vs. Whole-Body Vibration vs. Conventional Back-Strengthening Training in Chronic Non-specific Low Back Pain Patients: A Three-Armed Randomized Controlled Trial - Micke, Florian; Weissenfels, Anja; Wirtz, Nicolas; von Stengel, Simon; Dörmann, Ulrike; Kohl, Matthias; Kleinöder, Heinz; Donath, Lars; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
The aim of this multicenter trial was to compare the effects of Whole-Body Electromyostimulation (WB-EMS) and Whole-Body Vibration (WBV) with conventional back-strengthening training (CT) on changes in mean back pain intensity (MPI) and trunk strength in patients suffering from chronic non-specific low back pain (CNLBP). Two-hundred-forty CNLBP patients (40-70 years; 62% female) were randomly assigned to three intervention arms (WB-EMS: n=80 vs. WBV: n=80 vs. CT: n=80). All training intervention programs were performed for 12 weeks correspondingly to their usual commercial training setting. Before and during the last four weeks of the intervention MPI was recorded using a 4-week pain diary. Additionally, maximal isometric trunk extension and -flexion strength was assessed on the BackCheck® machine. A moderate but significant decrease of MPI was observed in all groups (WB-EMS: 29.7 ± 39.1% (SMD 0.50) vs. WBV: 30.3 ± 39.3% (SMD 0.57) vs. CT: 30.5 ± 39.6% (SMD 0.59); p < 0.001). Similar findings were observed for maximal isometric strength parameters with a significant increase in all groups (extension: WB-EMS: 17.1 ± 25.5% vs. WBV: 16.2 ± 23.6% vs. CT: 21.6 ± 27.5%; p<0.001; flexion: WB-EMS: 13.3 ± 25.6% vs. WBV: 13.9 ± 24.0% vs. CT: 13.9 ± 25.4%; p<0.001). No significant interaction effects for MPI (p=0.920) and strength parameters (extension: p=0.436; flexion: p=0.937) were observed. WB-EMS, WBV and CT are comparably effective in improving MPI and trunk strength in people with chronic unspecific low back-pain. However, WB-EMS was more time effective with a 43% or 62% lower training volume, compared with CT and WBV.